Influence of Thermal Parameters, Microstructure, and Morphology of Si on Machinability of an Al–7.0 wt.% Si Alloy Directionally Solidified - Cássio A. P. Silva; Layo R. M. Leal; Emanuelle C. Guimarães; Paulo M. Júnior; Antonio L. Moreira; Otávio L. Rocha; Adrina P. Silva (Advances in Materials Science and Engineering)
This study aims to correlate the influence of thermal and microstructural parameters such as growth rate and cooling rate (VL and TR) and secondary dendrite spacing (λ2), respectively, in the machining cutting temperature and tool wear on the necking process of the Al–7 wt.% Si alloy solidified in a horizontal directional device using a high-speed steel with a tungsten tool. The dependence of λ2 on VL and TR and dependence of the maximum cutting temperature and maximum flank wear on λ2 were determined by power experimental laws given by λ2 = constant (VL and TR)n and TMAX, VBMAX = constant (λ2)n, respectively. The maximum cutting temperature increased with increasing of λ2. The opposite occurred with the maximum flank wear. The role of Si alloying element on the aforementioned results has also been analyzed. A morphological change of Si along the solidified ingot length has been observed, that is, the morphology of Si in the eutectic matrix has indicated a transition from particles to fibers along the casting together with an increase of the particle diameters with the position from the metal/mold interface.